Cetuximab-Triptolide Conjugate Suppresses the Growth of EGFR-Overexpressing Lung Cancers through Targeting RNA Polymerase II - Keqiang Zhang; Yuelong Ma; Yuming Guo; Ting Sun; Jun Wu; Rajendra P. Pangeni; Min Lin; Wendong Li; David Horne; Dan J. Raz (Molecular Therapy: Oncolytics, 2020)
To overcome poor pharmacokinetics and toxicity of triptolide (TPL), a natural compound that exhibits potent anticancer activities, we developed a novel antibody-drug conjugate (ADC) to specifically deliver TPL to epidermal growth factor receptor (EGFR)-overexpressing non-small cell lung cancer (NSCLC) and others. The ADC (Cet-TPL) is made by conjugation of TPL to lysine residues of cetuximab (Cet), a clinically available anti-EGFR monoclonal antibody. Studies of antitumor efficacy demonstrated that Cet-TPL drastically suppressed in vitro proliferation and in vivo growth of these EGFR-overexpressing cancers, including NSCLC A549 and H1299 cells and two patient-derived xenografts, and head and neck squamous carcinoma UM-SCC6 cell, while it did not inhibit the proliferation and growth of NSCLC H520 that rarely expresses EGFR. Furthermore, immunofluorescence analysis revealed that Cet-TPL was effectively internalized and transported into lysosomes of EGFR-overexpressing cells. Cet-TPL effectively led to degradation of RNA polymerase II (Pol II) and demethylation of histone H3 lysines, and significantly induced apoptosis in these EGFR-overexpressing cancers. Compared with TPL, Cet, or their combination, Cet-TPL displayed higher target-specific cytotoxicity against EGFR-expressing cancers and much lower in vivo toxicity. In addition, Cet-TPL efficiently suppressed the activated EGFR pathway in UM-SCC6 cancer cells. Taken together, Cet-TPL represents a potent targeting therapeutic agent against EGFR-overexpressing NSCLC and others.